A survey of Colorado Plateau stream insect communities: the roles of riparian leaf litter and hydrologic variation on species growth and community structure - Moline, Angela B., author; Poff, N. LeRoy, advisor; Baron, Jill S., committee member; Kondratieff, Boris C., committee member; Merritt, David M., committee member; Theobald, David M., committee member (Colorado State University. Libraries, 2007)
Non-native saltcedar (Tamarix sp.) and Russian olive (Elaeagnus angustifolia) are now among the most common trees in western riparian zones, yet their effects on the growth of stream detritivores and the benthic community is largely unknown. I examined Tipula sp. growth on native (Populus) and non-native leaf litter in a laboratory experiment. Tipula larvae fed Tamarix were 1.7 and 2.5 times heavier than larvae fed Elaeagnus and Populus, respectively (Chapter 2). The Colorado Plateau of Utah, Arizona, Colorado and New Mexico is remote and one of the least studied regions in the USA from the perspective of stream ecology. I compared the ability of environmental and biological variables to explain the variance in benthic insect and riparian vegetation communities at 25 Plateau streams. Median particle size and the number of flood-free days were strong predictors of insect density and richness, but periphyton and leaf litter abundance were not. non-metric multidimensional scaling revealed three stream types (mountain, valley, and canyon streams) based on riparian species composition (Chapter 3). The hydrologic diversity of the Colorado Plateau makes it well suited to tests of habitat template theory; however, the stream hydrology of the region has not been characterized in an ecologically-meaningful way. I developed a conceptual model and classification system of unregulated Colorado Plateau streams based on two ecologically-relevant flow axes: flow permanence and flood regime. I was able to correctly classify streams into four classes (perennial-snowmelt, non-perennial-snowmelt, perennial-rain-driven, and non-perennial-rain-driven streams) based on ecologically-relevant hydrologic metrics and GIS-derived landscape variables with approximately 85% accuracy (Chapter 4). I addressed habitat template theory by testing the hypothesis that hydrologic disturbances (floods and droughts) are the major drivers of stream insect communities on the Colorado Plateau. I used family-level community metrics and six evolutionarily labile functional traits to test differences in the insect community assemblages in four stream classes. I found that disturbance-adapted taxa were common at all Colorado Plateau stream sites, but some insect traits (semi/univoltine, rare in drift, medium/large size) were more common in snowmelt-driven streams. I was able to predict snowmelt stream types from insect functional traits with 61% accuracy (Chapter 5).
Keywords: ecology; organismal biology; hydrologic sciences; limnology; entomology